KARAKTERISTIK JENIS KELAINAN REFRAKSI DI OPTIK OCCULAR TAHUN 2020 - Linawaty; Wahyu Budiana; Zakaria Efendi (Jurnal Mata Optik, 2022)
This study aimed to determine the characteristics of refractive errors that occur at the Occular optics at Tamini Square, East Jakarta. The population in this study were all glasses wearers who had refractive errors who came to Occular optics. This type of research is analytical descriptive with the sample being customers who come to Occular optics in 2020 involving 50 respondent. The process of taking data from the refraction book is grouped based on refractive errors and degrees and the data is processed using SPSS ver. 25. And the resulting magnitude of the prevalence for refractive errors of myopia is 48% (24 respondent), hypermetropia is 24% (12 respondent) and astigmatism is 28% (14 respondent) with mild, moderate and high degrees for myopia, mild degrees for hypermetropia and mild and moderate degrees for astigmatism